The Impact Of The Pre-Employment Card Program On Labor Force Participation In Indonesia (A Post-Covid-19 Analysis) - Abu Yazid; Marlina Ekawaty; Dias Satria (Proceedings of the 1st International Conference on Social Science (ICSS), 2024)
This study aims to examine the changes in labor absorption, particularly post-COVID-19, influenced by the Pre-Employment Card Program and sociodemographic characteristics. The main variable, the Pre-Employment Card Program, is analyzed based on recipients' status or those who have participated in training and received incentives. Sociodemographic characteristics include three variables: gender (using a dummy variable), education level (seven equivalent education levels), and age (25 to 44 years). Data from the National Labor Force Survey (Sakernas) for February 2022, conducted by the Central Bureau of Statistics (BPS) of Indonesia, is utilized. With a sample of 76,363 respondents aged 25 to 44 years, the study employs the binomial logit method to assess the influence of independent variables on changes in employment status. The results indicate that: a) the Pre-Employment Card Program has a smaller impact on employment compared to other variables, b) males are more likely to be employed than females post-pandemic, c) higher education levels increase the likelihood of employment, and d) older individuals are more likely to be employed or remain employed post-pandemic compared to younger individuals.